Developing Cognitive Conflict to Overcome Students’ Thinking Difficulties - Sumadji Sumadji; Timbul Yuwono (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
The purpose of this study is to describe the thinking difficulties of low-ability students. Low-ability students are those who can only reach score less than 66. The second objective is to know the effectiveness of cognitive conflict strategies in an effort to improve failed cognitive networks. The approach taken is qualitative with the type of classroom action research. In each action, it was applied the group learning strategy in the first session intended to explore additional thinking difficulties. In the second session their difficulties were overcome by implementing a cognitive conflict strategy. This research was completed in two actions based on the amount of material that consists of two parts. The research’s conclusions describe the basic difficulties of students’ thinking but are not summarized here. In this error, mostly students make their own formulas using distributive law on algebra. Another conclusion is that cognitive conflict strategies are effective at the level of 88.6% in overcoming thinking difficulties.